Radiology of non-spinal pain procedures a guide for the interventionalist - Syed, Mubin I. (Springer, 2011)
Most interventionalists are not radiologists and most radiologists do not understand interventional pain procedures. Nevertheless, interventionalists order extensive diagnostic imaging in the workup prior to any intervention. Against this background, this handy, well-illustrated manual has been designed to meet the major need of interventional pain physicians to understand the radiologic imaging involved in the performance of non-spinal pain procedures. It provides information on such topics as radiologic anatomy, the radiologic manifestations of indications and contraindications to interventional procedures, and the radiologic appearance of complications that may arise from these procedures. In addition, it will be useful for the diagnostic radiologist, who may be unaware of many of the interventional pain procedures. The chosen format will ensure that the reader is quickly able to reference any given procedure. Sections are devoted to the head and neck, thorax, abdomen, pelvis, and the upper and lower extremities. As this is a guidebook, it does not encompass every single pathologic entity that may be encountered; however, the commonly performed non-spinal pain procedures are included. This text will prove essential for any interventionalist who does not have easy access to a radiologist and vice versa.